2000
DOI: 10.1080/000164800750001125
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fungi in Sinus Fluid of Patients with Allergic Fungal Rhinosinusitis

Abstract: We aim to develop a rapid, accurate and sensitive diagnostic assay with which to detect the surface antigens of fungi thought to be involved in allergic fungal rhinosinusitis (AFRS), by assessing the usefulness of immunofluorescence microscopy (IMF) and enzyme linked immuno-absorbent assays (ELISA). The age, sex, clinical symptoms and signs, imaging (CT and/or MRI), microbiological subculture data, sinus contents, blood eosinophilia, aspergillosis precipitins, radioallergoabsorbent technology (RAST) for fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Karpovich-Tate et al reported that ELISA and pathological examination results are correlated in their preliminary study. 24 Fungal organisms detected in our study were Aspergillus, Cladosporium, Debaryomyces, Neurospora, Penicillium, and Ustilago. Our results are similar to data in the literature ( except for the absence of Alternaria.…”
Section: Discussionmentioning
confidence: 98%
“…Karpovich-Tate et al reported that ELISA and pathological examination results are correlated in their preliminary study. 24 Fungal organisms detected in our study were Aspergillus, Cladosporium, Debaryomyces, Neurospora, Penicillium, and Ustilago. Our results are similar to data in the literature ( except for the absence of Alternaria.…”
Section: Discussionmentioning
confidence: 98%
“…Direct count analyses of topsoil from various desert environments show that bacterial and viral populations range from ∼10 3 to 10 7 per gram (Gonzalez- Martin et al, 2013). Fungal populations typically occur at ∼10 6 per gram (Karpovich-Tate, 2000). Bacteria are present in wind eroded sediments in which the overall composition is determined by soil type and management, as well as dust particle size (Gardner et al, 2012).…”
Section: Biota In Dustmentioning
confidence: 99%
“…The remaining cases are attributed to the Aspergillus genus [ 48 ]. Routine, special, or immunofluorescence staining can help to increase the yield of fungal detection [ 49 ]. However, as false positives and false negatives can exist, fungal culture needs to be approached with caution [ 8 ].…”
Section: Reviewmentioning
confidence: 99%